TEACHING READING COMPREHENSIN OF SPOOF TEXT BY USING JIGSAW LEARNING MODEL TO THE ELEVENTH GRADE STUDENTS AT SMA NEGERI 13 PALEMBANG - Sri Yuliani (Program Studi Pendidikan Bahasa Inggris, 2019)
The objective of the study is to find out whether it is effective or not using jigsaw learning model in teaching reading comprehension of  spoof text to the eleventh grade students at SMA Negeri 13 Palembang. In this study, the researcher used experimental method. The population of this study is all the eleventh grade students at SMA Negeri 13 Palembang with the total numbers of students was 392. Therefore, the sample of the study is 72 students consist two classes,namely: 36 students for control group and 36 students for experimental group. The sample was taken by using non purposisve random sampling method. The data collected by using written test consist of 30 questions and the type of questions is multiple choice.  The result of the test was analyzed by using t-test which were pair sample t-test and independent sample t-test was known as: mean of post test in expermental group was 72.22 higher than past test mean score of control group was 58.64. Furthermore, the result of t-obtained was 6.132 and t-table was 2.030, it shows that t-obtained was higher than t-table. From the explanation above, there were significant difference between the experimental group that have been taught by using jigsaw learning model and control group that was not taught using treatment. It means that, Ho was rejected and Ha was accepted. It was concluded that it was effective of using jigsaw learning model to teach reading comprehension of spoof text to the eleventh grade students at SMA Negeri 13 Palembang.